Connecting Teaching and Research in Homoeopathy: Why and How? - Nayak, Chaturbhuja (Homœopathic Links, 2019)
Linking teaching with research in any stream is the need of the hour. Homoeopathy, being an integral part of health care delivery system in India and many other countries, goes no exception to it. Both teaching and research are inter-related, dependent and complementary to each other. Without quality teaching, research is like learning without curiosity, or like cataract surgery without restoring visual equity, or like studying Materia Medica without knowledge in Organon of Medicine. Similarly, sans high standard research, teaching in any medical discipline is like searching without direction, or like operating upon a human subject without knowing anatomy. In spite of the fact that some of the teaching institutions have taken up research projects and the outcomes of such research studies have been published in reputed medical journals, yet the quality of such articles needs further improvement. Many homoeopathy research organisations as well as the researchers, on certain aspects, have failed to update with the recent advancements in the field of education. Absence of mandatory provision for conducting research in teaching curriculum at undergraduate (UG) level and lack of proper training on research methodology and biostatistics at postgraduate (PG) level have led to the non-involvement of academicians and students in research studies. As a result, a void has been created in scientific publications by the faculty and students of homoeopathic colleges. The latest progresses in the field of research are useful for teaching of the individual subjects of UG and PG courses. The academicians as well as the researchers have to sit and discuss across the table the modalities of meaningful integration of teaching and research for mutual benefit. Hence, different facets of connecting teaching and research need to be deliberated upon to find out mutually acceptable solutions.
Keywords: homoeopathy; teaching; research; linkage need; linkage methods